KONTRA PERSEPSI TUAN GURU DAN TOKOH MAJELIS ADAT SASAK (MAS) LOMBOK TERHADAP PERNIKAHAN ADAT SASAK DAN IMPLIKASINYA BAGI MASYARAKAT SASAK - Salimul Jihad; Fathurrahman Muhtar (Universitas Islam Negeri Mataram, 2020)
The purpose of this research is to discuss the opinion and the legal position of indigenous wedding Sasak according to Tuan Guru and Masyarakat Adat Sasak (MAS) in Lombok. This research was field research, with an interethnic social stratification approach. This approach has proven that status groups are a community of lifestyle, recognised social identity, and publicly recognised honors or even social rankings. Researchers conducted a thorough interview (Indept interview) to several Tuan Guru and Tokoh Adat. In addition, researchers done observations to see the traditional Sasak wedding practice. Then, Data classified by its type and content. Data analysed with the qualitative analysis of Model Miles and Huberman, with the data reduction phases, data Display and conclusion verification. The main finding of this study is show the difference in views between Tuan Guru and Masyarakat Adat Sasak. The differences implicates the Sasak people to perform the wedding of Sasak customary rituals.